Domarens dilemma - motstridiga krav vid förlikningsförhandlingar enligt 42 kap. 17 § 1 st RB - Persson,Mikaela (2025)
This thesis examines tensions between civil procedure functions in Swedish law when judges exercise their discretion during settlement negotiations. The study focuses on Chapter 42, Section 17, Paragraph 1 of the Code of Judicial Procedure (RB), which obliges judges to facilitate settlements, and analyzes how these tensions manifest through the "Gothenburg model", a settlement method involving separate discussions with each party. Using coherence theory, the thesis analyzes three main functions of civil procedure: the legal protection function, the behavior guidance function, and the conflict resolution function. The analysis reveals fundamental tensions between these functions that create coherence deficits within the legal system. The findings demonstrate that Chapter 42, Section 17, Paragraph 1 RB represents a balancing attempt rather than a solution to functional tensions. The legislation prioritizes conflict resolution while attempting to preserve legal protection through flexible safeguards, but largely subordinates behavior guidance to party autonomy. The Gothenburg model, characterized by judges conducting separate conversations with parties, concretizes and amplifies these tensions by potentially compromising judicial neutrality and creating information management challenges. The study concludes that the tensions reflect an inherent hierarchy among civil procedure functions rather than systematic defects. While conflict resolution takes precedence and legal protection is balanced through adaptive mechanisms, behavior guidance remains marginalized. The coherence analysis re-veals that instead of creating mutual reinforcement between functions, the cur-rent system generates competing logics that judges must navigate without systematic guidance.
Keywords: processrätt; civilrätt; förlikning; koherens